2006
DOI: 10.1074/jbc.m601388200
|View full text |Cite
|
Sign up to set email alerts
|

Excess HDM2 Impacts Cell Cycle and Apoptosis and Has a Selective Effect on p53-dependent Transcription

Abstract: Mutational inactivation of p53 is only one of the ways that tumors lose p53 function. An alternate route is through overexpression of HDM2, the negative regulator of p53. To further understand how excess HDM2 regulates p53-mediated functions, we generated H1299 cell clones that constitutively express both ectopic HDM2 and tetracycline-regulated inducible p53. We found that over a range of p53 concentrations constitutively expressed HDM2 did not affect the levels of p53 protein. Nevertheless, cells with excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…In humans, MDM2 has been shown to be overexpressed in a subset of tumors; this overexpression is associated with accelerated cancer progression and lack of response to therapy in some tumor types (Freedman et al, 1999;Onel and CordonCardo, 2004). Consistent with these observations in human tumors, a human tumor cell line engineered to express just twofold more MDM2 displayed significantly weakened p53 activity, when compared to the parental cell line (Ohkubo et al, 2006).…”
supporting
confidence: 66%
“…In humans, MDM2 has been shown to be overexpressed in a subset of tumors; this overexpression is associated with accelerated cancer progression and lack of response to therapy in some tumor types (Freedman et al, 1999;Onel and CordonCardo, 2004). Consistent with these observations in human tumors, a human tumor cell line engineered to express just twofold more MDM2 displayed significantly weakened p53 activity, when compared to the parental cell line (Ohkubo et al, 2006).…”
supporting
confidence: 66%
“…Studies in cell culture have indicated a growth-suppressing function of Mdm2, but the molecular basis for this remains unclear (Brown et al 1998;Dang et al 2002). In one study, overexpression of Mdm2 altered the percent of cells arrested in the G1 versus the G2/M phases of the cell cycle in response to p53 (Ohkubo et al 2006). A requirement for Mdm2 in p53-dependent cell cycle arrest via the cyclin-dependent kinase inhibitor p21 has also been suggested (Giono and Manfredi 2007).…”
Section: Mdm2 As An Oncogene: Inactivation Of the Wild-type Tumor Supmentioning
confidence: 99%
“…For instance, it should be noted that endogenously expressed Mdm2 can be found at promoters such as p21 (Minsky and Oren 2004;Arva et al 2005;Ohkubo et al 2006;White et al 2006;Tang et al 2008), negatively influencing p53's transcriptional output. The mechanism by which this occurs is unclear, but perhaps Mdm2 functions through recruitment of the histone deacetylases KAP1 (Wang et al 2005) and HDAC1 (Ito et al 2002), the disruption of HAT interactions with p53 (Ito et al 2002;Jin et al 2004), or the monoubiquitylation of histone H2B within the vicinity of the p53 RE (Minsky and Oren 2004).…”
Section: Transcriptional Regulation By P53mentioning
confidence: 99%